Pengembangan Manajemen Entrepreneur Potensi Pariwisata dan UMKM Dalam Meningkatkan Pendapatan Masyarakat Desa Barania - Madzlina, Madzlina; Winadia, Winadia; Azizah, Azizah; Khafifa, Ummul; Riska, Riska; Anugrawati, Anugrawati; Rahmawati, Rahmawati; Nurpasirah, Nurpasirah; Armanto, A.; Yudiyanti, Ervina; Asdar, Muhammad; Purnama, Hendra Arya; Nurpaisah, Nurpaisah; Asrul, Asrul; Nurlinda, Nurlinda; Pratama, Ahmad Aditya; Makmur, Makmur (Abdimas Universal, 2025)
Barania Village is one of the villages located in West Sinjai District, which has significant tourism and Small, Micro, and Medium Enterprises (MSME) potential but has not been fully exploited. With tourist attractions such as Galung Village and Salu Birayya Waterfall, this village offers opportunities to increase people's income. However, the challenges faced include weak human resource management and a lack of innovation in managing tourism and MSMEs. The Student Organization Capacity Strengthening Program (PPK ORMAWA) from Muhammadiyah Sinjai University aims to provide training and assistance in tourism management and MSME development. Through this initiative, it is hoped that there will be an increase in community knowledge and creativity, as well as the formation of a widely known local brand. The output of this program includes development guidebooks, new products, and an increase in the number of visitors to the village, thereby encouraging sustainable local economic growth.